THE OPINIONS AND PREFERENCES OF THE EUROPEAN BUYERS ON THE FURNITURE AND FURNITURE ACCESSORIES MARKET - PETRACHE (LANG), Beatrice Georgeta; ISMANA-ILISAN, Camelia Maria; CRETOIU, Raluca (Annals of Spiru Haret University. Economic Series, 2019)
In this article we aim to analyze the preferences and opinions of European furniture buyers in the context of Germany, Italy, Poland, France and Austria being among the top 10 world furniture manufacturers, accounting for over 19% of the world production and 60% of the European one. We have developed this research given that the furniture industry is an important sector in the economy, employing about one million people at the level of the European Union, in 130,000 companies in the field. The furniture segment is also well represented in the field of innovation also, accounting for 12% of the applications for design registration in the European Union Intellectual Property Office (EUIPO).  This also reflects on the production of furniture, currently 2/3 of the world’s leading peak production coming from Europe. The research is of a quantitative nature, the technique adopted is the interview, and the research tool is the questionnaire. The purpose of the research is to identify the way and the level at which European consumers’ value furniture accessories in the general context of furniture quality assessment in conjunction with the need for accessory information.